PENERAPAN MEDIA SOSIAL UNTUK MENINGKATKAN EKSISTENSI BUDAYA KARAWITAN DI DUSUN KANOMAN YOGYAKARTA - Ningrum, Dyaloka Puspita; Arifin, Tommy Satriadi Nur; Putra, Ariandi (Universitas Mataram, 2024)
The development of social media with all its creativity can be used as a strategy to strengthen local cultural products which are starting to be marginalized in today's modern era. The practice of playing gamelan musical instruments, which is synonymous with musical culture, especially among Javanese people, has become increasingly marginalized over time. In fact, traditional art is actually one of the riches of the Indonesian nation. This Community Service activity aims to encourage residents in Kanoman Hamlet, Yogyakarta, to survive and at the same time pioneer a movement in maintaining the traditional art of karawitan which is full of historical and philosophical values ​​using lecture, discussion and direct mentoring methods. This activity was carried out in January 2024 with a total of 60 participants, including involving one of the arts activist groups at that location. It is hoped that the results of the activities will be sustainable in forming a cultural icon of Kanoman Hamlet. The consistency of residents in these places must also be optimized through potential social media management, especially through packaging narrative messages and creating contemporary audio-visual content. So real contributions from all parties are really needed, so that the musical culture itself can continue to exist so that it is able to compete in the global world.